Association of Multimodal Pain Management Strategies with Perioperative Outcomes and Resource Utilization: A Population-based Study. (May 2018) - Memtsoudis, Stavros G.; Poeran, Jashvant; Zubizarreta, Nicole; Cozowicz, Crispiana; Mörwald, Eva E.; Mariano, Edward R.; Mazumdar, Madhu
Abstract : Background: Multimodal analgesia is increasingly considered routine practice in joint arthroplasties, but supportive large-scale data are scarce. The authors aimed to determine how the number and type of analgesic modes is associated with reduced opioid prescription, complications, and resource utilization. Methods: Total hip/knee arthroplasties (N = 512, 393 and N = 1, 028, 069, respectively) from the Premier Perspective database (2006 to 2016) were included. Analgesic modes considered were opioids, peripheral nerve blocks, acetaminophen, steroids, gabapentin/pregabalin, nonsteroidal antiinflammatory drugs, cyclooxygenase-2 inhibitors, or ketamine. Groups were categorized into "opioids only" and 1, 2, or more than 2 additional modes. Multilevel models measured associations between multimodal analgesia and opioid prescription, cost/length of hospitalization, and opioid-related adverse effects. Odds ratios or percent change and 95% CIs are reported. Results: Overall, 85.6% (N = 1, 318, 165) of patients received multimodal analgesia. In multivariable models, additions of analgesic modes were associated with stepwise positive effects: total hip arthroplasty patients receiving more than 2 modes (compared to "opioids only") experienced 19% fewer respiratory (odds ratio, 0.81; 95% CI, 0.70 to 0.94; unadjusted 1.0% [N = 1, 513] vs . 2.0% [N = 1, 546]), 26% fewer gastrointestinal (odds ratio, 0.74; 95% CI, 0.65 to 0.84; unadjusted 1.5% [N = 2, 234] vs . 2.5% [N = 1, 984]) complications, up to a –18.5% decrease in opioid prescription (95% CI, –19.7% to –17.2%; 205 vs . 300 overall median oral morphine equivalents), and a –12.1% decrease (95% CI, –12.8% to –11.5%; 2 vs . 3 median days) in length of stay (all P < 0.05). Total knee arthroplasty analyses showed similar patterns. Nonsteroidal antiinflammatory drugs and cyclooxygenase-2 inhibitors seemed to be the most effective modalities used. Conclusions: While the optimal multimodal regimen is still not known, the authors' findings encourage the combined use of multiple modalities in perioperative analgesic protocols. Abstract : Using a Premier Perspective database of total hip and knee arthroplasties, patients were grouped into "opioids only" and 1, 2, or more than 2 additional modalities. There was a stepwise modality number-associated decrease in opioid patient-controlled analgesia use, opioid prescriptions, and some opioid-related side effects, but not cost of hospitalization. The strongest association was for cyclooxygenase-2 inhibitors and nonsteroidal antiinflammatory drugs.Supplemental Digital Content is available in the text.